Disentangling molecular alterations from water-content changes in the aging human brain using quantitative MRI - Shir Filo (Nature Portfolio, 2019)
MRI has been used for the non-invasive imaging of human brain aging but is sensitive to both tissue molecular composition and water content. Here the authors present a quantitative MRI method that discriminates these factors and describe region-specific changes in the molecular composition of the aging human brain.